Study on Security and Privacy in 5G-Enabled Applications. (21st December 2020) - Qiu, Qin; Liu, Shenglan; Xu, Sijia; Yu, Shengquan
Abstract : 5G applications face security risks due to the new technology used and the performance requirements of the specific application scenario. This paper analyzes the security requirements and presents hierarchical solutions for stakeholders to build secure 5G applications. First, we summarize the technical characteristics and typical usage scenarios of 5G. Then, we analyze the security and privacy risks faced by 5G applications and related security standards and research work. Next, we give the system reference architecture and overall security and privacy solutions for 5G applications. Based on the three major application scenarios of eMBB, uRLLC, and mMTC, we also provide specific suggestions for coping with security and privacy risks. Finally, we present a use case of industrial terminal access control and make conclusions of this paper.